Signs of continuity : the function of miracles in Jesus and Paul - Rhodea, Greg, 1983- (Bulletin for biblical research supplements, 2019)
"Explores the debate over whether Paul was a faithful follower of Jesus or a corruptor of Jesus's message. Focuses on an element of similarity between the two men: the place of miracles in their ministries"--Provided by publisher